Neurologic outcome of postanoxic refractory status epilepticus after aggressive treatment. (4th December 2018) - Beretta, Simone; Coppo, Anna; Bianchi, Elisa; Zanchi, Clara; Carone, Davide; Stabile, Andrea; Padovano, Giada; Sulmina, Endrit; Grassi, Alice; Bogliun, Graziella; Foti, Giuseppe; Ferrarese, Carlo; et al.
Abstract : Objective: To investigate neurologic outcome of patients with cardiac arrest with refractory status epilepticus (RSE) treated with a standardized aggressive protocol with antiepileptic drugs and anesthetics compared to patients with other EEG patterns. Methods: In the prospective cohort study, 166 consecutive patients with cardiac arrest in coma were stratified according to 4 independent EEG patterns (benign, RSE, generalized periodic discharges [GPDs], malignant nonepileptiform) and multimodal prognostic indicators. Primary outcomes were survival and cerebral performance category (CPC) at 6 months. Results: RSE occurred in 36 patients (21.7%) and was treated with an aggressive standardized protocol as long as multimodal prognostic indicators were not unfavorable. RSE started after 3 ± 2.3 days after cardiac arrest and lasted 4.7 ± 4.3 days. A benign EEG pattern was recorded in 76 patients (45.8%); a periodic pattern (GPDs) was seen in 13 patients (7.8%); and a malignant nonepileptiform EEG pattern was recorded in 41 patients (24.7%). The 4 EEG patterns were highly associated with different prognostic indicators (low-flow time, clinical motor seizures, N20 responses, neuron-specific enolase, neuroimaging). Survival and good neurologic outcome (CPC 1 or 2) at 6 months were 72.4% and 71.1% for benign EEG pattern, 54.3% and 44.4% for RSE, 15.4% and 0% for GPDs, and 2.4% and 0% for malignant nonepileptiform EEG pattern, respectively. Conclusions: Aggressive and prolonged treatment of RSE may be justified in patients with cardiac arrest with favorable multimodal prognostic indicators.